A Bibliometric Analysis of Servant Leadership for Future Research - Ahmad Idris; Nafisatul Zairoh (Universitas Gadjah Mada, 2022)
Introduction/Main Objectives: This study is to provide a wider bibliometric literature review on servant leadership (SL). Background Problems: SL requires a comprehensive review of existing studies. Looking for potential topics is one way to develop knowledge in SL by using bibliometric studies. Novelty: This paper is to fill in the gaps by providing an extensive bibliometric analysis of the literature related to SL. Research Methods: We analyzed 368 articles published from January 1, 2011 until July 12, 2021, a 10 year period. Articles were taken from the Scopus database. We have tried to classify articles using VOSviewer software. Finding/Results: The bibliometric analysis is done to identify the development in the total number of SL publications, SL articles mostly cited, top journals in SL research, most productive authors in SL research, most countries publishing SL research, and subject area of SL publications. SL studies were classified into nine clusters. From each cluster, the trend shows that SL studies are mostly done on terms that have many occurrences and link strengths. From the overlay visualization analysis for the new year, opportunities for future research such as perceived organizational support, psychological capital, work engagement, life satisfaction, and emotional intelligence for SL emerge. Conclusion: This article is the second servant leadership bibliometric study with a different database and complements the first. This article explores the development of servant leadership research. Some of the keywords found using VosViewer become opportunities for future research.